Antecedents of Trust in Brand Post on Brand Awareness and it Impacts to Purchase Intention - Jordan Jeremy; Ferdi Antonio (Enrichment : Journal of Management, 2021)
This research aimed to analyze the affect of informative value, entertainment value, expertise, trustworthiness, attractiveness and similarity from trust in brand posts variables and its impact to brand awareness and purchase intention. PLS-SEM used to evaluate the empirical data obtained by purposive sampling and earned 273 respondents who met requirements through a questionnaire which distributed online. The results indicate that from this four of antecedents, namely informative value, entertainment value, trustworthiness and similarity along with mediating variable trust in brand post had a positive and significantly affect to brand awareness and purchase intention. The strongest affect was occured in similarity and informative value. Meanwhile, the strongest direct effect on purchase intention was found on brand awareness. It said that positive affect from brand awareness on purchase intention was higher than trust in brand post to purchase intention, thus the results of this research were confirmed the theory of consumer trust in influencing brand awareness and consumer intention in making purchases.